Flood simulation using shuttle radar topographic mission digital elevation model in Hadejia River Basin, Nigeria - Kazaure, Abubakar Sani (2013)
In order to reduce the effect of food, many research works have been conducted in various regions while others are ongoing. In most cases unavailability of detailed cross section data affected the accuracy of food studies in many developing nations and hindered application of advanced modelling tools. In this study, Hadejia River cross sections were created using Shuttle Radar To-pographic Mission Digital Elevation Model (SRTM DEM) and HEC-GeoRAS in Geographic Information System (GIS) environment. The 90m SRTM DEM used was produced by NASA, downloadable free from US Geological Survey, DIVA-GIS, CGIAR Consortium for Spatial Information and many similar databases for different parts of the world. The Triangulated Irregular Network (TIN) for the study area was created in GIS environment and used for creating the geometry data covering the stream centreline, banks and flowpath lines, reach lengths, cross sections and stations details. Hydraulic modelling of the river was performed with HEC-RAS using HEC-GeoRAS extracted river geometry data imported from GIS to compute the water level and °ood extent. The 2001 discharge of 690 m3/s was used in the modelling along with the Manning roughness coe±cients of 0.065 for the channel and 0.15 for the foodplain with an expansion and contraction coe±cients of 0.1 and 0.3 respectively. Upon successful run of the model, cross sections output plot, water surface pro¯le plot, XYZ perspective and the fooded areas were determined. The HEC-RAS results were further processed in GIS environment facilitated by HEC-GeoRAS to produce the food inundation map of the study area. An overlay of the food inundation map obtained from the study showed the food water covers most of the villages affected in recent foods with the highest inundation observed at far down stream of the reach near Hadejia. To protect those areas affected by the food, embankment levees were proposed at such locations. The study shows that the cross sections obtained using the SRTM-DEM give the required geometry data for an analysis in HEC-RAS. Despite the fact that the cross sections obtained using the 90m SRTM-DEM can provide the required geometry data for use in HEC-RAS and creation of the inundation map of the area, the cross sections are not very accurate and it is recommended that more accurately measured cross section data need to be obtained for future flood studies in the basin.